(untitled) (Spectrum of Humanities and Social Sciences, 2025)
This paper examines the nature of occupational shift of Hill Dalit communities of Kaski District, Nepal. These artisanal communities have historically been caste based and marginalized. They are facing changes and pressures from social reform and the impacts of a market-based economy. The objectives of this research are to analyze the livelihood practices of Hill Dalits in Kaski District and to investigate how market-based adaptations have contributed to shifts in their socioeconomic position. This study is based on primary data collected from 72 purposively selected Dalit households. The data is analyzed by integrating quantitative and qualitative methods. The findings show changing patterns among Dalits in micro-entrepreneurship, schooling, informal wage work, and international labor migration. Developmental efforts such as public education and job training have supported these livelihood opportunities. The structural barriers, such as caste discrimination and limited institutional access still prevent upward mobility for Dalit community. The research found a gradual reconstruction of the definition of caste and caste-based occupation. Younger generations are increasingly rejecting inherited caste-based roles. Findings of this research on changing pattern of livelihood among Dalits provide a foundation for future investigations on social transformation. It may support academia by explaining social transformation among marginalized communities and how broader livelihood options support to social change.